Tingkatan Layanan E-Government Melalui Aplikasi “Monggo Lapor” di Kantor Humas Pemerintah Kota Magelang - Joko Tri Nugraha; Dwi Wahyu Ningsih (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2020)
The low quality of public services provided by the apparatus is a bad image of the government in the community. Problems related to the government are related to the services received by the City Government of Magelang. Electronic government is modern, which facilitates the interaction of government and society in the administration of public government. Through the application monggo report, government relations for the community are used to help with the government and provide advice and criticism about the City of Magelang. The purpose of this study was to analyze the level of e-government services through the application monggo report the field of public complaints and information in the Public Relations of the Regional Secretariat of the City of Magelang. This research uses descriptive qualitative. Data collection methods through observation, interviews and documentation. Data analysis uses an interactive model, by collecting data collection, data reduction, data presentation and conclusion collection. The data validity technique uses the triangulation of data and sources. The results showed that the level of e-government services in the form of one-way, two-way communication and transactions was good enough and provided information to the public through websites, social media and online newspapers..